Gems of Identity: Unveiling Female Archetypes, Cultural Narratives, and the Facets of Womanhood in Lebanese Jewelry Advertising - Khoury, Josiane El (Journal of Cultural Analysis and Social Change, 2025)
This study examines how jewelry advertising in Lebanon constructs female archetypes and negotiates cultural narratives of womanhood through distinct branding strategies. Drawing on McCracken’s Meaning Transfer Model [1], Gobé’s Emotional Branding Theory [2], and Jung’s Archetype Theory [3], the research compares two campaigns: Zoughaib & Sons featuring celebrity Haifa Wehbe, and Moukarzel’s “J’ai Envie.” The analysis reveals how Zoughaib relies on celebrity endorsement to project archetypes of glamour, seduction, and authority, while Moukarzel employs emotional appeal to foreground individuality, love, and self-expression. By situating these portrayals within the framework of Sustainable Development Goal 5 (Gender Equality), this study highlights the dual role of advertising as both a commercial tool and a cultural text that influences gender representation. The findings underscore how commercials shape consumer psychology while simultaneously negotiating the multiplicity of women’s identities in contemporary Lebanese society.